Macronyssus diversipilis - Orlova, Maria V.; Anisimov, Nikolay V. (Zenodo, 2023)
Macronyssus diversipilis (Vitzthum, 1920) Distribution – Russia (Stanyukovich 1997), Europe (Radovsky 1967; Haitlinger 1978), Caucasus (Dagestan republic) (Orlova et al. 2020b). Hosts – Myotis daubentonii (Radovsky 1967; Haitlinger 1978), My. nattereri (Radovsky 1967; Haitlinger 1978), My. tschuliensis (Orlova et al. 2020b), My. myotis (Haitlinger 1978; Stanyukovich 1997), My. dasycneme (Stanyukovich 1990), My. brandtii (Haitlinger 1978; Stanyukovich 1990), Pipistrellus pipistrellus (Radovsky 1967), Vespertilio murinus (Radovsky 1967), Plecotus auritus (Radovsky 1967), Eptesicus nillsonii (Stanyukovich 1997), E. serotinus (Stanyukovich 1997), Barbastella barbastellus (Haitlinger 1978). Published as part of Orlova, Maria V. & Anisimov, Nikolay V., 2023, Three new species of bat-parasitic gamasid mites of the genera Spinturnix, Macronyssus and Steatonyssus (Acari: Mesostigmata: Spinturnicidae, Macronyssidae) from Siberia and Mongolia, with keys to species of Russia and adjacent countries, pp. 211-239 in Persian Journal of Acarology 12 (2) on page 224, DOI:10.22073/pja.v12i2.76740, http://zenodo.org/record/8113590